CONTRIBUTION OF WIFE AND CHILD OF LABOUR FISHERMAN IN MEETING HOUSEHOLD INCOME IN MEDAN BELAWAN DISTRICT, MEDAN CITY, NORTH SUMATERA PROVINCE - Marganda Tohonan Lubis; Hamdi Hamid; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTResearch on the Contribution of Wife and Child of Labour Fisherman in Meeting Household Income was conducted in July 2019 in Medan Belawan District, Medan City, North Sumatra Province. This study was aimed to describe the activities carried out by children and fishermen and analyze children and children at home. The method used in this research is survey method and the number of respondents in this study were 44 respondents.From the results of the research analysis, it was found that the activities carried out by the wife and children of fishermen in fulfilling household income, most of them trade and sell services. Budgetary contributions of wives and children are 42.77% in the medium category. The biggest contribution is the wife of a fisherman who works as a trader, amounting to 86%, which means the fishermen's wife has a very important role in increasing household income.Keywords: contribution, income, household